2011
DOI: 10.1055/s-0031-1297070
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Characterization of the Binding Process of Sulindac to Human Serum Albumin

Abstract: This study deals with the molecular basis of the binding of the anti-inflammatory drug sulindac (CAS 38194-50-2) to human serum albumin (HSA) using high-performance liquid affinity chromatography. The chromatography was carried out using a HSA-immobilized column and a predominantly aqueous mobile phase (67 mmol/l sodium phosphate buffer/propan-1-ol, 94:6 v/v). A small quantity of sulidac was injected onto the column while increasing concentrations of the same drug were added to the mobile phase. The capacity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Nearly 15 % of the retention of PBZ is due to the competitive binding with SUL. The relationship between 1/(k'-X) and [SUL] in the mobile phase is linear till [SUL] of 4 µmol/l which coincides with the concentration of SUL-binding sites previously reported (4.5−4.7 × 10 -6 mol/l) [5]. This behavior suggests a single site competition between PBZ and SUL for these sites.…”
Section: Competition Between Sul and Pbzsupporting
confidence: 88%
See 2 more Smart Citations
“…Nearly 15 % of the retention of PBZ is due to the competitive binding with SUL. The relationship between 1/(k'-X) and [SUL] in the mobile phase is linear till [SUL] of 4 µmol/l which coincides with the concentration of SUL-binding sites previously reported (4.5−4.7 × 10 -6 mol/l) [5]. This behavior suggests a single site competition between PBZ and SUL for these sites.…”
Section: Competition Between Sul and Pbzsupporting
confidence: 88%
“…3, and their linearity is an indication that the standard enthalpy change is essentially constant over the investigated temperature range. The binding characteristics of SUL and PBZ during their competitive binding are presented in Table 1 together with the respective values for SUL in the absence of PBZ [5].…”
Section: Competition Between Sul and Pbzmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic study on the binding of sulindac to HSA by means of HPLAC suggested spontaneous binding with a high negative G. Both H and S were negative, and the absolute value of H highly exceeded the entropy term T S. Therefore it was supposed that the binding was dominated by hydrogen bonds and salt linkages while hydrophobic interactions were of less importance. These data allowed hypothesis to be made about the nature of the binding site and the binding mechanism [103,144]. Thermodynamic study also revealed different binding mechanisms for R-and S-WAR, responsible for the observed stereodiscrimination by the common binding site on HSA [144].…”
Section: Thermodynamic Characterization Of Drug -Hsa Bindingmentioning
confidence: 93%
“…The separation temperature is one of the main determinant factors that can affect selectivity, resolution, retention factor and even the elution order of enantiomers during HPLC enantioseparations [34,35]. To investigate the effects of temperature and to gain a better understanding of the mechanistic aspects of the enantiodiscrimination process on the Chiral-HSA column, thermodynamic analysis was performed in a 10 mM phosphate buffer/IPA 96/4 v/v% mixture.…”
Section: Effect Of the Temperature-thermodynamic Analysismentioning
confidence: 99%